An EPCH Control Strategy for Complex Nonlinear Systems with Actuator Saturation and Disturbances - Meng, Xiangxiang; Yu, Haisheng; Zhang, Jie (Information sciences, 2023)
•A new smooth saturation function with hyperbolic tangent is adopted to deal with the limitations between the actuator and the control signal.•A NDOB is utilized to resolve the influence of model parameter uncertainty, measurement error and external disturbance in real complex systems.•To enhance the control accuracy for the target, we propose a novel EPCH control strategy, which adopts adaptive gain technology and variable damping injection technology. This paper presents a novel error port-controlled Hamiltonian (EPCH) strategy with adaptive gains for a class of complex nonlinear systems subject to actuator saturation and disturbances. Considering the actuator saturation phenomenon in real complex systems, a new smooth saturation function with hyperbolic tangent is adopted to deal with the limitations between the actuator and the control signal. A nonlinear disturbance observer (NDOB) is utilized to compensate the influence of model parameter uncertain, noise, measurement error, external disturbance and other factors in real complex systems. To enhance the accuracy of position control and tracking control for the target, we propose a novel EPCH strategy, which adopts adaptive gain and variable damping technology in the damping injection link. Finally, the permanent magnet synchronous motor (PMSM) servo system is applied to verify the proposed method. The strategy proposed compared with port-controlled Hamiltonian based on disturbance observer, port-controlled Hamiltonian based on load torque estimator and other methods has better control performances by simulation results.